2003
DOI: 10.1097/00000542-200307000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of Bispectral Index in Sedated Intensive Care Unit Patients Revealed by Administration of Muscle Relaxant

Abstract: The BIS in sedated intensive care unit patients may be lower with paralysis for an equivalent degree of sedation because of high muscular activity. The magnitude of BIS overestimation is significantly correlated to both BIS and electromyographic activity before neuromuscular blockade. The authors conclude that clinicians who determine the amount of sedation in intensive care unit patients only from BIS monitoring may expose them to unnecessary oversedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(142 citation statements)
references
References 38 publications
1
137
0
3
Order By: Relevance
“…Humans sedated or anaesthetized with propofol alone also have higher BIS values than when propofol is administered in conjunction with a non-depolarizing muscle relaxant. These higher values have been attributed to electromyographic (EMG) activity that Laboratory Animals (2006) 40 falsely increases the BIS value (Bruhn et al 2000, Vivien et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Humans sedated or anaesthetized with propofol alone also have higher BIS values than when propofol is administered in conjunction with a non-depolarizing muscle relaxant. These higher values have been attributed to electromyographic (EMG) activity that Laboratory Animals (2006) 40 falsely increases the BIS value (Bruhn et al 2000, Vivien et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…18 When non-paralyzed patients received sedation in an intensive care unit, use of the BIS to guide administration of midazolam exposed the patients to "unnecessary oversedation." 19 Thus, it would appear that in spontaneously breathing patients, the EMGrelated "contamination" of the BIS value eliminates the beneficial effects of BIS monitoring in improving the titration of the maintenance volatile anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Although bispectral index monitoring has been evaluated for conscious sedation, results to date for this indication have been variable. 25,26 In conclusion, we have demonstrated that a remifentanil technique combining a basal infusion and PCA boluses and propofol target infusion were adequate, but not optimal techniques for RF ablation.…”
Section: Discussionmentioning
confidence: 84%